National population prevalence of antibodies to SARS-CoV-2 among pregnant women in Scotland during the second wave of the COVID-19 pandemic: a prospective national serosurvey. (October 2021) - McAuley, A.; Gousias, P.; Hasan, T.; Rashid, L.; Richardson, C.; Reid, G.; Templeton, K.; McGuire, J.; Wise, H.; McVicar, L.; Jenks, S.; Gunn, R.; et al.
Abstract: Objectives: This study aimed to determine SARS-CoV-2 seroprevalence among pregnant women in the Scottish population during the second wave of the COVID-19 pandemic. Study design: Prospective national serosurvey. Methods: We tested 13, 428 residual samples retrieved from pregnant women participating in the first trimester combined ultrasound and biochemical screening for fetal trisomy across Scotland for SARS-CoV-2 antibodies over a 6-month period from November 2020 to April 2021. Seroprevalence estimates were adjusted for the sensitivity and specificity of the assays and weighted to reference populations. Results: Seroprevalence rates in the antenatal samples significantly increased from 5.5% (95% confidence interval [CI] 4.7%–6.5%) in the 5-week period up to and including International Organization for Standardization (ISO) Week 51 (w/b Monday 14 December 2020) to 11.3% (95% CI 10.1%–12.6%) in the 5-week period up to and including ISO Week 14 (w/b Monday 5 April 2021). Increasing seroprevalence trends across the second wave were observed among all age groups. Conclusions: By the end of the second wave of the COVID-19 pandemic, approximately one in 10 women tested around the end of the first trimester of pregnancy had antibodies to SARS-CoV-2, suggesting that the vast majority were still susceptible to COVID-19 as they progressed to the later stages of pregnancy, when risks from infection are elevated for both mother and baby.